The Effects of a 7000-Step Goal and Weekly Group Walking Program for Overweight and Obese Elderly People in Sarawak, Malaysia: A Quasi-experimental Study - Mohd Fakhree Saad; Whye Lian Cheah; Helmy Hazmi (Korean Society for Preventive Medicine, 2021)
Objectives: Physical inactivity is the fourth leading global risk factor for mortality, followed by obesity. The combination of these risk factors is associated with non-communicable diseases, impaired physical function, and declining mental function. The World Health Organization recommends physical activity to reduce the mortality rate. Thus, this study examined the effects on anthropometric measurements of a 12-week walking program for elderly people in Samarahan, Sarawak, Malaysia with a 7000-step goal and weekly group walking activities. Methods: A quasi-experimental study was conducted involving 109 elderly people with a body mass index (BMI) ≥25.0 kg/m2. BMI, body composition, and average daily steps were measured at baseline, 6 weeks, and 12 weeks. Data were analyzed using SPSS version 26.0, and repeated-measures analysis of variance with the paired t-test for post-hoc analysis was conducted. Results: In total, 48 participants in the intervention group and 61 participants in the control group completed the study. A significant interaction was found between time and group. The post-hoc analysis showed a significant difference between pre-intervention and post-intervention (within the intervention group). The post-intervention analysis revealed an increase in the mean number of daily steps by 3571.59, with decreases in body weight (-2.20 kg), BMI (-0.94 kg/m2), body fat percentage (-3.52%), visceral fat percentage (-1.29%) and waist circumference (-2.91 cm). Skeletal muscle percentage also showed a significant increase (1.67%). Conclusions: A 12-week walking program combining a 7000-step goals with weekly group walking activities had a significant effect on the anthropometric measurements of previously inactive and overweight/obese elderly people.